TECHNOLOGICAL ASPECTS OF RUSSIAN ENERGY DIPLOMACY - S. Z. Zhiznin; V. M. Timokhov (Vestnik MGIMO-Universiteta)
In the present study we examined the impact of technology on the development of world energy in the world, as well as on the development of international energy relations. The important role of international cooperation in the field of energy technologies as a key factor in the development and global deployment of energy technologies in the industry. The most effective technology in the world of multilateral cooperation under the auspices of the International Energy Agency (IEA) and other international organizations. It allows the joint efforts of the countries concerned to develop new technologies, test them and implement in production. For Russia, it is very important, because at the moment our country is not only a leading exporter of energy resources, but also has a significant impact on global energy security. At the same time Russia's FEC requires urgent and serious modernization through the development and introduction of innovative technologies on the basis of the study of international experience. Therefore the question of modernization of Russian fuel and energy complex has an international character. One way to accelerate the process of modernization of the organization is a public-private partnership that will largely depend on the nature and possibilities of Russian energy diplomacy, given the geopolitical and economic realities in connection with the sanctions imposed by Western countries against our country.